Population- and Species-Based Variation of Webworm–Parasitoid Interactions in Hogweeds (Heracelum spp.) in the Netherlands. Issue 4 (27th May 2020) - Harvey, Jeffrey A; Ode, Paul J; Gols, Rieta
Abstract: In three Dutch populations of the native small hogweed ( Heracleum sphondylium L. [Apiales: Apiaceae]), and one of the invasive giant hogweed ( H. mantegazzianum Sommeier & Levier [Apiales: Apiaceae]), interactions between a specialist herbivore, the parsnip webworm ( Depressaria radiella ), and its associated parasitoids were compared during a single growing season. We found host plant species-related differences in the abundance of moth pupae, the specialist polyembryonic endoparasitoid, Copidosoma sosares, the specialist pupal parasitoid, Barichneumon heracliana, and a potential hyperparasitoid of C. sosares, Tyndaricus scaurus Walker (Hymenoptera: Encyrtidae). Adult D. radiella body mass was similar across the three small hogweed populations, but moths and their pupal parasitoid B. heracliana were smaller when developing on giant than on small hogweeds where the two plants grew in the same locality (Heteren). Mixed-sex and all-male broods of C. sosares were generally bigger than all-female broods. Furthermore, adult female C. sosares were larger than males and adult female mass differed among the three small hogweed populations. The frequency of pupal parasitism and hyperparasitism also varied in the different H. sphondylium populations. These results show that short-term (intra-seasonal) effects of plant population on multitrophic insects are variable among different species in a tightly linked food chain.